THE APPLICATION OF ENGLISH IN FOREIGN TOURIST SERVICES AT ACEH TSUNAMI MUSEUM - Nurul Kamaliah; Helmiyadi; Menalisa (English Education Department, 2019)
After the Tsunami disaster in 2004in Aceh, it provided a great opportunity for the province to be known to the world. Tourism has become one of the sectors that is growing and in demand by foreigners. The tourism object of Aceh Tsunami Museum Aceh is proven to be able to attract a number of tourists which has increased significantly from year to year. One of the supports of the success of tourism is the role of capable and reliable guides in the service sector. Especially thatguides who use English to interact with foreign tourists. Seeing the important the role of English for the advancement of tourism, this research needs to be carried out with the aim of analyzing the understanding and quality of guides to the English language used in their field of work, as well as analyzing the obstacles found in the field in terms of communicating with English. The research subjects were guides and the head of guides at the Aceh Tsunami Museum. This study used qualitative research with a descriptive research design. The data collection techniques used areobservation, documentation, and interview. The results showed that the application and quality of guides to English language skills when guiding foreign tourists was quite good. Some of the obstacles faced by guides in implementing English when communicating with foreign tourists are different pronunciations and accents, unstructured training, and guides do not guide regularly.